2022
DOI: 10.3389/fpls.2022.944066
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the contribution of small molecule-based biostimulants to the biofortification of maize in a water restriction scenario

Abstract: Biostimulants have become an asset for agriculture since they are a greener alternative to traditionally used plant protection products. Also, they have gained the farmers’ acceptance due to their effect on enhancing the plant’s natural defense system against abiotic stresses. Besides commercially available complex products, small molecule-based biostimulants are useful for industry and research. Among them, polyamines (PAs) are well-studied natural compounds that can elicit numerous positive responses in drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 86 publications
(107 reference statements)
1
0
0
Order By: Relevance
“…The enhanced agronomic performance of plants treated with PBBs corresponds with the results of previous studies, primarily using protein hydrolysates but, in some cases, amino acids on a range of different plant types [14,20,21,33,34,[41][42][43]. Additionally, small molecules such as polyamines have been reported to improve growth and stress tolerance ability in plants [44]. Previous studies have also reported positive physiological responses in terms of photosynthetic parameters in different crops from the use of PBBs [45,46], which our results verified.…”
Section: Discussionsupporting
confidence: 89%
“…The enhanced agronomic performance of plants treated with PBBs corresponds with the results of previous studies, primarily using protein hydrolysates but, in some cases, amino acids on a range of different plant types [14,20,21,33,34,[41][42][43]. Additionally, small molecules such as polyamines have been reported to improve growth and stress tolerance ability in plants [44]. Previous studies have also reported positive physiological responses in terms of photosynthetic parameters in different crops from the use of PBBs [45,46], which our results verified.…”
Section: Discussionsupporting
confidence: 89%